Revisiting the Trade-off Between Risk and Incentives: The Shocking Effect of Random Shocks? - Corgnet, Brice; Hernán-González, Roberto (Management Science, 2019)
Despite its central role in the theory of incentives, empirical evidence of a trade-off between risk and incentives remains scarce. We reexamine this trade-off in a workplace lab environment and find that, in line with theory, principals increase fixed pay while lowering performance pay when the relationship between effort and output is noisier. Unexpectedly, agents produce substantially more in the noisy environment than in the baseline despite weaker incentives. In addition, principals’ earnings are significantly higher in the noisy environment. We show that these findings can be accounted for when agents maximize a non-CARA utility function or when they exhibit loss aversion. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2914 . This paper was accepted by Uri Gneezy, behavioral economics.